(untitled) (CIPEEX, 2024)
OPENENERGY IS SOFTWARE THAT AIMS TO PRESENT INFORMATIVE AND UTILITARIAN SOFTWARE, WHOSEPURPOSE IS TO PROVIDE PERTINENT DATA ABOUT CLEAN AND SUSTAINABLE ENERGY SOURCES. FURTHERMORE,THIS SOFTWARE IS CAPABLE OF ASSISTING USERS IN ACCURATELY CALCULATING THE COST OF THE ELECTRICITYBILL, BASED ON AN ESTABLISHED AVERAGE CONSUMPTION, IN ADDITION TO PROVIDING A CAREFULCOMPARATIVE ANALYSIS BETWEEN CONVENTIONAL ELECTRICITY AND SUSTAINABLE ENERGY, AIMING TO ANAPPRECIATION OF THE COST-BENEFIT INVOLVED IN EACH ENERGY OPTION. IT IS WORTH NOTING THAT, IN ACOMPLEMENTARY WAY, THE PRODUCT IN QUESTION ALSO INCLUDES THE OFFER OF PERSONALIZEDRECOMMENDATIONS FROM PARTNER COMPANIES SPECIALIZED IN THE INSTALLATION OF SOLAR PANELS, WHICHCONSTITUTE A VIABLE AND EFFICIENT ALTERNATIVE FOR THE ADOPTION OF RENEWABLE ENERGY SOURCES. INTHIS WAY, THE AFOREMENTIONED SOFTWARE CONTRIBUTES TO RAISING AWARENESS AND PROMOTING THE USEOF CLEAN ENERGY SOURCES, BY PROVIDING RELEVANT INFORMATION, SUPPORT IN MAKING FINANCIALDECISIONS AND GUIDANCE ON RELIABLE COMPANIES FOR IMPLEMENTING SUSTAINABLE SOLUTIONS. THEOBJECTIVE OF THE SOFTWARE IS TO EDUCATE, RAISE AWARENESS, CARRY OUT COST CALCULATIONS AND PROVIDEFACILITIES IN THE TRANSITION PROCESS TO CLEANER AND MORE RENEWABLE ENERGY SOURCES. TO THIS END,METHODOLOGIES WILL BE ADOPTED BASED ON RESEARCH AND INFORMATION COLLECTION, DEFINITION OFREQUIREMENTS, DESIGN AND ARCHITECTURE, SOFTWARE DEVELOPMENT, DATA INTEGRATION, LAUNCH ANDOBTAINING USER FEEDBACK, AS WELL AS CARRYING OUT MAINTENANCE AND UPDATE ACTIVITIES. THESESTEPS MAKE UP THE STRUCTURING AND IMPLEMENTATION OF THE PROPOSED WEBSITE. THE METHODOLOGYADOPTED FOR THE DEVELOPMENT OF THIS STUDY IS SCRUM, AN AGILE APPROACH WIDELY RECOGNIZED ANDUSED IN PROJECT MANAGEMENT. SCRUM IS BASED ON ITERATIVE AND INCREMENTAL WORK CYCLES, INWHICH ACTIVITIES ARE DIVIDED INTO SPRINTS, AIMING FOR CONTINUOUS DELIVERY OF VALUE THROUGHOUT THEPROCESS. USING SCRUM AS A METHODOLOGY BRINGS SIGNIFICANT ADVANTAGES FOR THE DEVELOPMENT OF UNIVERSIDADE EVANGÉLICA DE GOISCIPEEX - CONGRESSO INTERNACIONAL DE PESQUISA, ENSINO E EXTENSOV.4 (2023) - ISSN: 2596-15782THE PROPOSED SOFTWARE. IT ALLOWS FOR GREATER FLEXIBILITY AND ADAPTATION TO CHANGES THROUGHOUT THEPROCESS, PROMOTES COLLABORATION AND EFFECTIVE COMMUNICATION BETWEEN TEAM MEMBERS, ANDPROVIDES GREATER VISIBILITY AND TRANSPARENCY INTO PROJECT PROGRESS. THERE IS A GROWING DEMANDFOR INFORMATION AND SOLUTIONS RELATED TO CLEAN AND SUSTAINABLE ENERGY. USERS ARE INCREASINGLYINTERESTED IN UNDERSTANDING THE ENVIRONMENTAL AND ECONOMIC BENEFITS OF RENEWABLE ENERGYSOURCES. THE GOAL IS TO CONTINUE TO IMPROVE AND EXPAND THE INFORMATION BASE ON CLEAN ENERGYSOURCES, INCLUDING DETAILS ON EMERGING TECHNOLOGIES AND INNOVATIONS IN THE SECTOR. THIS WILLALLOW USERS TO ACCESS UP-TO-DATE AND RELEVANT DATA ON SUSTAINABLE ENERGY. THIS VIEW CAN AFFECTTHE COMPARISON BETWEEN CONVENTIONAL ELECTRICAL ENERGY AND CLEAN ENERGY AND IS A VALUABLETOOL FOR USERS TO EVALUATE THE COSTS AND BENEFITS OF EACH OPTION. USERS WANT TO UNDERSTAND THEFINANCIAL AND ENVIRONMENTAL IMPLICATIONS BEFORE MAKING INFORMED DECISIONS. THE SOFTWARE CANENHANCE FUNCTIONALITY FOR COMPARING CONVENTIONAL ELECTRIC POWER TO CLEAN ENERGY BY INCLUDINGADDITIONAL METRICS SUCH AS CARBON FOOTPRINT AND POTENTIAL GREENHOUSE GAS EMISSIONS SAVINGS.THIS WILL ALLOW USERS TO HAVE A MORE COMPLETE AND INFORMED VIEW WHEN CHOOSING BETWEENOPTIONS.